Phytochemical studies and biological activities of selected Piper species - Irna Syairina, binti Sahari (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The composition of essential oils from P. nigrum varieties (Kuching, Semongok Emas, Semongok Perak, Semongok Wan, Semongok Aman, 27283 and 841 varieties), P. aduncum, P. porphyrophyllum and one unknown Piper species (noted as Piper P13) found in Sarawak were studied. The essential oils were extracted by hydrodistillation and their chemical constituents were characterized by Gas Chromatography-Mass Spectrometer (GC-MS). β-Caryophyllene was identified in all essential oils and used as a chemical marker for Piper species. δ-Elemene, α-caryophyllene and δ-cadinene were commonly detected in all essential oils of P. nigrum varieties. Phenylpropanoids (apiol and dill apiole) occurred significantly in P. aduncum essential oil, whereas lactones (-palmitolactone and -stearolactone) were only identified in P. porphyrophyllum essential oil and β-farnesene was detected mainly in Piper P13 essential oil. Hierarchical cluster analysis (HCA) and principal component analysis (PCA) on essential oils data of the studied Piper species showed strong relationships in term of chemical profiles of essential oil from P. nigrum varieties. Several chemical similarities of essential oil components were observed from different Piper species. The stems and roots of P. nigrum and P. aduncum were extracted sequentially using hexane, dichloromethane, ethyl acetate and methanol. 2,4-Di-tert-butylphenol, methyl hexadecanoate, 9-oxo-10,12-octadecadienoic acid, piperine, ethyl piperonylcyanoacetate, β-sitosterol and 3α,7β-dihydroxy-5β,6α-epoxycholestane were identified as the principal compounds in P. nigrum extract, while 1-nonadecanol, 1-tetracosanol, 2,4-di-tert-butylphenol and 1-docosanol were detected as the main compounds in P. aduncum extract. Biological activities studies against termite (Coptotermes sp.) showed that the combined fractions from hexane and dichloromethane extracts from P. nigrum, as well as the methanol extract from P. aduncum root displayed significant anti-termite activities (LC50 ranged <0.100 – 8.150%). Antimicrobial tests on P. nigrum and P. aduncum extracts against bacteria (S. aureus, S. typhi, E. aerogenes and B. cereus), microfungi (Aspergillus niger, A. flavus and Candida albicans) and macrofungi (Trichoderma sp., Botrytis sp., Fusarium sp. and Glomerella cingulata) presented different degree of inhibition. Antibacterial activities shown by the hexane and dichloromethane fractions from P. nigrum and P. aduncum extracts were more effective. In contrast, most of the tested extracts were inactive against microfungi and macrofungi. Only P. nigrum extracts displayed bioactivities against Trichoderma sp.. Most of the extracts from P. nigrum and P. aduncum were proven toxic with LC50 values ranged between 1.897 – 74.131 μg/mL in the toxicity assessment against Artemia salina larvae. GC-MS analysis presented amides, terpenoids and carboxylic acid as the main components in the bioactive combined fractions of P. nigrum, while phenolic compounds, sterols and alcohols were frequently identified in bioactive combined fractions of P. aduncum.